Serotonin 2019
DOI: 10.5772/intechopen.77956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects Related to Plasma Serotonin in the Horse

Abstract: Serotonin (5-HT) is a neurotransmitter that has important functions such as the physiological regulation of hemostasis, blood clotting, bone metabolism, cardiovascular growth, contractile activity and gastrointestinal motility, renal function, and stress and sexual behavior, among others. In this review, we consider the potential of 5-HT to contribute to the development of various pathological conditions, including metabolic, vascular, and nervous disorders in horses. The values of 5-HT in circulation are modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…It should be noted that even in healthy horses, reported reference values for 5-HT are not consistent (Satué, Gardon, & Marcilla, 2018). One possible explanation for this inconsistency is the use of different biological samples and analytical methods for 5-HT determination, as high-pressure liquid chromatography (HPLC) and radioimmunoassays (RIA) (Ayala et al, 2012) since that in our study ELISA was the technique used.…”
Section: Discussionmentioning
confidence: 73%
“…It should be noted that even in healthy horses, reported reference values for 5-HT are not consistent (Satué, Gardon, & Marcilla, 2018). One possible explanation for this inconsistency is the use of different biological samples and analytical methods for 5-HT determination, as high-pressure liquid chromatography (HPLC) and radioimmunoassays (RIA) (Ayala et al, 2012) since that in our study ELISA was the technique used.…”
Section: Discussionmentioning
confidence: 73%
“…In mammals, there have been numerous studies relating plasma serotonin levels to stress and other disorders. However, as shown in the extensive review of their relation to various pathological states in horses (54), the picture in relation to stress is confusing. Nevertheless, a study of plasma serotonin levels in dairy cows showed the values to be elevated by the stress of negative energy balance (55).…”
Section: Introductionmentioning
confidence: 99%